HUBUNGAN ANTARA KEPUASAN DAN LOYALITAS MAHASISWA UNIVERSITAS BUNDA MULIA - Lelly Christin (Universitas Bunda Mulia, 2017)
Business world growth in rapid speed nowadays, because of that reason all the companies in business world try to make a differentiation strategy in order to be different than other company. One of important aspect which concern by all companies is customer satisfaction. Customer satisfaction is a part of company management, because of that those companies realize if they could fulfil this aspect they could have a profit. But, we can’t just rely on customer satisfaction to improve long term benefits. Loyal customer will not turn around to other similar companies. University must to construct customer loyalty. Loyal customers, in this case students usually give a positive recommendation (the likehood of spreading positive word of mouth).Key Words- Satisfaction, Loyality, Student